THE ANALYSIS OF STUDENTS’ WRITING ABILITY OF PROCEDURE TEXT BY USING READ EXAMINE DECIDE WRITE (REDW) STRATEGY AT THE GRADE VIII OF SMP NEGERI 4 PADANGSIDIMPUAN - Abdul Rahman Siagian (Universitas Muhammadiyah Tapanuli Selatan, 2026)
The research was conducted by the researcher at the Grade VIII of SMP Negeri 4 Padangsidimpuan. The aims of this research was to find out Students’ Writing Ability of Procedure Text Text by using Read, Examine, Decide, and Write (REDW) Strategy at the Grade VIII of SMP Negeri 4 Padangsidimpuan. In order to achieve the purpose of this research, the writer carried out in quantitative approach by applying descriptive method. The population of this research was the Grade VIII of SMP Negeri 4 Padangsidimpuan. They were 183 students, the writer used cluster sampling technique to get the sample. The samples were 32 students. The procedure text was applied as the instrument of this research, the writer used percentage formula. Based on the data that has been analyzed, it can be found that (1) students’ writing procedure text ability by using Read Examine Decide Write (REDW) Strategy to the grade VIII of SMP Negeri 4 Padangsidimpuan had an improvement. The improvement from 64.7 to 76.6. It meant that there was the improvement about 11.9%. Therefore, it was not a big improvement but it had passed from the minimal criteria and (2) the factors that affect students’ problem in writing procedure text ability by using Read Examine Decide Write (REDW) Strategy to the grade VIII of SMP Negeri 4 Padangsidimpuan was generic structure. The students felt difficult in determining goals, material and steps (use of communicative sequence, imperative sentence, numbering, and vocabulary).